13,14-Dihydro-15-Keto Prostaglandin F-2 alpha Release in Response to Oxytocin Challenge Early Post-Partum in Anoestrous Nelore Cows Submitted to Temporary Calf Removal and Progesterone Priming - Satrapa, R. A. [UNESP]; Pinheiro, V. G. [UNESP]; Ereno, Ronaldo Luiz [UNESP]; Membrive, C. M. B. [UNESP]; Piagentini, M. [UNESP]; Binelli, M.; Barros, C. M. [UNESP] (Wiley-Blackwell, 2010)
The study evaluated, in early post-partum anoestrous Nelore cows, if the increase in plasma oestradiol (E2) concentrations in the pre-ovulatory period and/or progesterone priming (P4 priming) preceding ovulation, induced by hormonal treatment, reduces the endogenous release of prostaglandin PGF(2)alpha and prevents premature lysis of the corpus luteum (CL). Nelore cows were subjected to temporary calf removal for 48 h and divided into two groups: GPE/eCG group (n = 10) and GPG/eCG group (n = 10). Animals of the GPE/eCG group were treated with a GnRH agonist. Seven days later, they received 400 ID of eCG, immediately after PGF(2)alpha treatment, and on day 0, 1.0 mg of oestradiol benzoate (EB). Cows of the GPG/eCG group were similarly treated as those of the GPE/eCG group, except that EB was replaced with a second dose of GnRH. All animals were challenged with oxytocin (OT) 9, 12, 15 and 18 days after EB or GnRH administration and blood samples were collected before and 30 min after OT. Irrespective of the treatments, a decline in P4 concentration on day 18 was observed for cows without P4 priming. However, animals exposed to P4 priming, treated with EB maintained high P4 concentrations (8.8 +/- 1.2 ng/ml), whereas there was a decline in P4 on day 18 (2.1 +/- 1.0 ng/ml) for cows that received GnRH to induce ovulation (p < 0.01). Production of 13,14-dihydro-15-keto prostaglandin F-2 alpha (PGFM) in response to OT increased between days 9 and 18 (p < 0.01), and this increase tended to be more evident in animals not exposed to P4 priming (p < 0.06). In conclusion, the increase in E2 during the pre-ovulatory period was not effective in inhibiting PGFM release, which was lower in P4-primed than in non-primed animals. Treatment with EB promoted the maintenance of elevated P4 concentrations 18 days after ovulation in P4-primed animals, indicating a possible beneficial effect of hormone protocols containing EB in animals with P4 priming.